AKOMODASI KOMUNIKASI ANTAR SUKU AKIT DAN SUKU JAWA DI DESA SUKA MAJU KECAMATAN BANTAN KABUPATEN BENGKALIS - Annisa Nurjannah; Nova Yohana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Humans as social beings interact with each other both with different cultural backgrounds and the same, such as the Akit tribe and tribal Javanese immigrants in the village of Suka Maju Bantan District Bengkalis who mingle with each other. In the process of interaction, both tribes have difficulty when adjusting from boat verbal and nonverbal forms to accommodate cultural between the two tribes. The purpose of this research is to know the strategy of convergence, divergence strategy and excessive accommodation strategy at Akit Tribe and Java Tribe in Suka Maju Village Bantan District Bengkalis in communicating.This research uses qualitative method with symbolic interaction approach. The location of this research is in Suka Maju Village Bantan District Bengkalis Regency. Subjects in this study were Akit Tribe and Java Tribe as 17 people obtained by Snowball Sampling technique. Data collection techniques are done through observation, in-depth interviews and documentation. The data analysis technique using Interactive model of Huberman & Miles.The results of this study indicate that at the time of the communication accommodation between Akit Tribe and Java Tribe in Suka Maju Village Bantan district Bengkalis, there are 3 forms of strategy they are (1) Convergence strategy of verbal form is by using Malay language and language controlled by both tribes when interacting, while for nonverbalnya form is using body movements that are created to provide comfortable when interacting. (2) Sterategi divergensi, for verbal form there is no attempt to use the language of his interlocutor, and the nonverbalnya form is Akit Tribe and Java Tribe doing movements of cultural rejection, there is no effort to reduce the speed and tone of voice. (3) The accommodation strategy of the grotes is that the Java Tribe makes a mistake in using the tone of speech, so the Akit Tribe uses the opposite language at the wrong time, it is part of the verbal form. For its nonverbal form Akit Tribe performs excessive movements when communicating with the Java Tribe.